Multi-resolution wavelet analysis of high time resolution millimeter wavelength observations of solar bursts - Giménez de Castro, C. G. (2001)
By means of the wavelet representation of multi-resolution analysis, we study millimeter wavelength (mm-w) radio solar bursts obtained at 48 GHz with high time resolution (<=8 ms); observed at Itapetinga (Brazil). The multi-resolution analysis decomposes the signal locally both in time and in frequency, allowing us to identify the different temporal structures which underlie the flux density time series and the transient phenomena characteristic of solar bursts. The analysis was applied to the flux time profile of four solar bursts observed at a mm-w, studying separately the pre-flare, impulsive and post-flare phases when possible. We find that a wide range of time scales contributes to the radio flux. The minimum time scale found for the impulsive phase is 32 ms, after which the noise dominates the emission; the maximum is 8 s. Pre- and post-flare phases have a minimum time scale of 256 ms and a maximum between 1 to 8 s. Multi-resolution ``spectral indexes'', which are a measure of the self-similar behavior of the signal, are in some cases bigger for the impulsive phase than for the pre- and post-flare phases. We find that as the flux becomes higher the contribution from shorter time scales is enhanced.